2021
DOI: 10.1177/15347346211052811
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leukocyte-Platelet-Rich Fibrin in Promoting Wound Healing in Diabetic Foot Ulcers

Abstract: To explore the effect of leukocyte-platelet-rich fibrin (L-PRF) on promoting wound healing in diabetic foot ulcers. A total of 42 patients with diabetic foot ulcers at our hospital from January 2017 to July 2020 were retrospectively analyzed. A control group and a PRF group were established. The two groups of patients underwent debridement. In the platelet-rich fibrin (PRF) group, autologous L-PRF was used to cover ulcer wounds. One time each week, Vaseline gauze was used to cover the ulcer wounds. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…PRF is a safe, appropriate, easy-to-use adjunctive treatment modality with substantial possibility for the management of chronic skin wounds like pressure, diabetic foot, or venous-leg ulcers without any adversative effects. [ 27 , 28 ] However, studies have suggested that the reduced or compromised wound healing capacity in uncontrolled diabetic patients may be due to a reduction in growth factors and prolonged inflammatory responses due to increased proinflammatory cytokines in T2DM patients. [ 22 , 29 , 30 ] Thus, a modification in the protocol (rpm and time) for obtaining PRF in diabetic patients may be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…PRF is a safe, appropriate, easy-to-use adjunctive treatment modality with substantial possibility for the management of chronic skin wounds like pressure, diabetic foot, or venous-leg ulcers without any adversative effects. [ 27 , 28 ] However, studies have suggested that the reduced or compromised wound healing capacity in uncontrolled diabetic patients may be due to a reduction in growth factors and prolonged inflammatory responses due to increased proinflammatory cytokines in T2DM patients. [ 22 , 29 , 30 ] Thus, a modification in the protocol (rpm and time) for obtaining PRF in diabetic patients may be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It is relevant, however, to determine how much fibrinogen is in each fraction and the yield of clottable components present to predict the ability of liquid PRF to generate PRF membranes that are presumably easier to handle than standard PRF where the time between vein puncture and centrifugation is a critical determinant of the size of solid PRF [ 24 ]. These liquid PRF-derived membranes may be prepared in larger quantities and even stored in a cooling environment until their use, which may be more ideal for the treatment of diabetic wounds [ 25 ]. PRF membranes can be customized in shape into larger-sized membranes by pooling of PPP and BC from various tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PRF has been used as an adjuvant in treating wounds (e.g., diabetic foot) to form a protective barrier to increase local cellular activity, causing tissue recovery. 3 This action is due to PRF's tissue regeneration potential. 4 PRF's involvement in wound healing may go beyond acting as a protective barrier.…”
Section: Introductionmentioning
confidence: 99%